Rv3091, An Extracellular Patatin-Like Phospholipase in Mycobacterium tuberculosis, Prolongs Intracellular Survival of Recombinant Mycolicibacterium smegmatis by Mediating Phagosomal Escape - Cui, Ziyin; Dang, Guanghui; Song, Ningning; Cui, Yingying; Li, Zhe; Zang, Xinxin; Liu, Hongxiu; Wang, Zhongxing; Liu, Siguo (Frontiers in Microbiology, 2020)
Patatin-like phospholipases (PLPs) are important virulence factors of many pathogens. However, there are no prevailing studies regarding PLPs as a virulence factor of Mycobacterium tuberculosis (Mtb). Analysis of Rv3091, a putative protein of Mtb, shows that its belongs to the PLPs family. Here, we cloned and expressed the rv3091 gene in M. smegmatis, and subsequently conducted protein purification and characterization. We show that it possesses phospholipase A1, phospholipase A2. and lipase activity. We confirm the putative active site residues, namely, Ser214 and Asp407, using site directed mutagenesis. The Rv3091 is an extracellular protein that alters the colony morphology of M. smegmatis. The presence of Rv3091 enhances the intracellular survival capability of M. smegmatis in murine peritoneal macrophages. Additionally, it promotes M. smegmatis phagosomal escape from macrophages. Moreover, Rv3091 significantly increased the survival of M. smegmatis and aggravated lesions in C57BL/6J murine lungs in vivo. Taken together, our results indicate that Rv3091 as an extracellular patatin-like phospholipase that is critical to the pathogenicity of mycobacterium as it allows mycobacterium to utilize phospholipids for its growth and provides resistance to phagosome killing, resulting in its enhanced intracellular survival.